We are starved: poems - Kryah, Joshua, author; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2011)
We Are Starved introduces an important poetic vision, a surprising and exciting voice.
The poor know they are poor -- We are starved -- It survives, a way of harming, your mouth -- Sallied forth -- The least child -- We will be fed upon, we will be fed -- Languor, succor, ardor -- The body-hole -- Ghostmeat -- Therefore that he may raise, the Lord throws down -- The body in its final commerce -- Playlist of the same -- Love like unto whited sepulchres -- Chanticleer -- Noli me tangere -- This plenty, this never enough -- Cheapside -- A paradise -- Miracle of the drowned -- Corpus Christi carol -- Many are the ruined cathedrals of the heart -- That man to man is an arrant wolfe -- From the gospel of the foundering -- Thinking one place could not two bodies bear -- The day without before this without -- Darkling -- An attraction to distance and disappearance -- Poor dogsbody, poor dogsbody's body -- I had not brought you into the world for love for naught -- Things fast toward their absent forms -- Homecoming -- Centaur -- Nobody is ever missing -- And naught I have and all the world I seize upon -- We are starved -- Extinct animals looking for a home
Keywords: American poetry -- 21st century